Reliability Analysis of Large Span Cable-stayed Bridges Based on Support Vector Machine. Issue 5 (February 2020) - Wang, Yu; Duan, Kaikai; Liu, Laijun; Guo, Hongchao
Abstract: a method of combining the support vector machine and the intelligent algorithm to perform reliability analysis on large span cable-stayed bridges was proposed in this paper. The algorithm is verified by an example, which shows that the algorithm has higher precision and can be extended to the actual project. Therefore, this paper takes Jiangmen North Street Waterway Bridge as the engineering background, uses the finite element software ANSYS to establish the cable-stayed bridge model and MATLAB software to compile the intelligent algorithm and data processing. It mainly analyzes the reliability of the main beam mid-span deflection, the cable stress and main tower stress of the North Street Waterway Bridge. Finally, the general limit range method is used to estimate the reliability index of the North Street waterway bridge structure system. The results show that the cable stay failure has the greatest impact on the reliability of the entire structural system, so it is necessary to pay attention to the maintenance and monitoring of stay cables.